(3efgL GdJejR GdGSJQGJjLj h GdGLJeGYj ddefXeGJs - (3HTQi gGTe(B, (3GdYRGhjs; (3GMeO Ydj UGdM(B, (3GHQGgje Ndjd GHQGgjes ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3GdefXeGJ h GdGOGQI hGdPcGA eY GdJWQb Gdi CfhGY GdPcGA GdGSJQGJjLj hGdTYhQj h GdJfGaSj PGJ GdGQJHGW GdeHGTQ hGdUejej HYed GdefXeGJs
(3eQGLY(B: (3dcd aUd eQLYs
Keywords: (3EOGQI GdGYeGds; (3GdPcGAs; (3GdefXeGJs